Digitalizing Performance-Based Assessment: Preservice English Teachers' Perception and Readiness - Femilia, Praptika Septi; Yusuf, David Ilham (UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
Digitalization becomes a current issue in English language teaching. It gives influences to many aspects in instructional, including in assessment. Meanwhile, performance-based assessment (PBA) is considered as another issue in case of its subjectivity and complicated implementation. In EFL context, many studies noted positive perception on the use of digitalization for PBA delivered by English teachers. Yet, rare similar studies are conducted to preservice teachers. This study aims to explore preservice teachers’ perception and readiness on the use of digitalization for PBA. It is a quantitative study by employing descriptive quantitative research design. Eleven preservice teachers were purposively included as the subjects of the study. Data were collected by using a 5-likert-scale questionnaire with 21 questions. Then, it was analyzed by concerning on mean score and standard deviation. The findings show that preservice English teachers perceived digitalization on PBA very well and they were ready to apply digital PBA on their future real classes.